2015
DOI: 10.1007/s11739-015-1368-4
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with mortality in patients presenting to the emergency department with severe hypernatremia

Abstract: Hypernatremia is a common electrolyte disorder associated with prolonged hospitalization and death. Severe hypernatremia is defined as a serum sodium (Na(+)) concentration >160 mmol/L. To the best of our knowledge, there is little information on patients with severe hypernatremia, Na(+) >160 mmol/L. Therefore, in this study, we aimed to determine the frequency, demographic and clinical characteristics, comorbid conditions and treatment strategies in patients presenting to the emergency department with severe h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…In the largest cohort published to date to determine the effect of hypernatremia correction rate in critically ill patients (11)(12)(13), we found that rapid correction of both admission and hospital-acquired hypernatremia occurred in a third of patients, and that rapid correction .0.5 mmol/L per hour or .12 mmol/L per day was not associated with in-hospital mortality or cerebral edema. In fact, there were no cases of cerebral edema in the 78 patients who had serum sodium correction of .12 mmol/L per day.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…In the largest cohort published to date to determine the effect of hypernatremia correction rate in critically ill patients (11)(12)(13), we found that rapid correction of both admission and hospital-acquired hypernatremia occurred in a third of patients, and that rapid correction .0.5 mmol/L per hour or .12 mmol/L per day was not associated with in-hospital mortality or cerebral edema. In fact, there were no cases of cerebral edema in the 78 patients who had serum sodium correction of .12 mmol/L per day.…”
Section: Discussionmentioning
confidence: 79%
“…However, the data to support this rate of correction is negligible (9). The studies in adults with hypernatremia showed that rapid sodium correction rates associated with less mortality (11,13). Alshayeb et al (12) and Ates et al (13) used .0.134 and $0.25 mmol/L per hour as a rapid hypernatremia correction rates, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to hyponatremia, hypernatremia was associated with increased mortality in patients undergoing percutaneous endoscopic gastrostomy [ 39 ], cardiothoracic surgery [ 40 ], or cardiac transplantation; in hip fracture patients [ 31 ]; in patients with chronic kidney disease [ 25 ]; in critically ill patients [ 41 43 ]; and in patients with traumatic brain injuries [ 33 , 44 ]. The reported mortality rate varies greatly, ranging from as low as 5.2% to as high as 82% [ 45 54 ]. This discrepancy is mainly due to data from elderly patients [ 46 , 47 , 49 , 50 ] and on which cutoff value is used to define hypernatremia [ 51 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…The reported mortality rate varies greatly, ranging from as low as 5.2% to as high as 82% [ 45 54 ]. This discrepancy is mainly due to data from elderly patients [ 46 , 47 , 49 , 50 ] and on which cutoff value is used to define hypernatremia [ 51 54 ]. However, using a study population similar to ours, Leung et al reported hypernatremia in 2.2% of surgical patients compared with 1% in our population and a mortality rate of 5.2%, which is close to our 9.16% mortality rate [ 12 ].…”
Section: Discussionmentioning
confidence: 99%